(untitled) (American Journal of Islam and Society, 2010)
Rania Al-Baz’s ten-chapter book touches on a sore point found all over the globe and among people of all socioeconomic classes. Written in the first person, she intersperses her story with reports on the laws and customs in Islam and in Saudi society that shed light on the events in her life. The reader becomes acquainted with her life philosophy, which helped her overcome the difficulties she faced and the physical and mental pain she endured. Through her personal story we learn how Arabs perceive relations between the sexes, Saudi women’s place in society and the home, women’s absolute submission to their husbands and their desires, and the Qur’anic law concerning such crimes as murder (p. 8) and the physical abuse of women ...